Contribution of adipocyte Na/K-ATPase α1/CD36 signaling induced exosome secretion in response to oxidized LDL - Pillai, Sneha S.; Pereira, Duane G.; Zhang, Jue; Huang, Wenxin; Beg, Mirza Ahmar; Knaack, Darcy A.; de Souza Goncalves, Bruno; Sahoo, Daisy; Silverstein, Roy L.; Shapiro, Joseph I.; Sodhi, Komal; Chen, Yiliang (Frontiers in Cardiovascular Medicine, 2023)
Adipose tissue constantly secretes adipokines and extracellular vesicles including exosomes to crosstalk with distinct tissues and organs for whole body homeostasis. However, dysfunctional adipose tissue under chronic inflammatory conditions such as obesity, atherosclerosis, and diabetes shows pro-inflammatory phenotypes accompanied by oxidative stress and abnormal secretion. Nevertheless, molecular mechanisms how adipocytes are stimulated to secrete exosomes under those conditions remain poorly understood. In this work, we report that CD36, a scavenger receptor for oxidized LDL, formed a signaling complex with another membrane signal transducer Na/K-ATPase in adipocytes. The atherogenic oxidized LDL induced a pro-inflammatory response in in vitro differentiated mouse and human adipocytes and also stimulated the cells to secrete more exosomes. This was largely blocked by either CD36 knockdown using siRNA or pNaKtide, a peptide inhibitor of Na/K-ATPase signaling. These results showed a critical role of the CD36/Na/K-ATPase signaling complex in oxidized LDL-induced adipocyte exosome secretion. Moreover, by co-incubation of adipocyte-derived exosomes with macrophages, we demonstrated that oxidized LDL-induced adipocyte-derived exosomes promoted pro-atherogenic phenotypes in macrophages, including CD36 upregulation, IL-6 secretion, metabolic switch to glycolysis, and mitochondrial ROS production. Altogether, we show here a novel mechanism through which adipocytes increase exosome secretion in response to oxidized LDL and that the secreted exosomes can crosstalk with macrophages, which may contribute to atherogenesis.